Diagnóstico e tratamento da epicondilite lateral do cotovelo no Brasil. Estudo transversal - Lazarini, Rafael Fuchs [UNIFESP] (2021)
Purpose: Lateral epicondylitis (LE) or tennis elbow is the most common elbow painful condition. There are various possibilities described in the literature, without evidence to support a gold standard management. Objective: To evaluate how the Brazilian orthopedist diagnoses and treats lateral epicondylitis. Methods: This is a cross-sectional study. A questionnaire has been prepared for information to the participants at three major Brazilian congresses of orthopedists in 2018, with eight specific questions about diagnosis and treatment. The results were analyzed in accordance with the overall number of responses, and were evaluated among three groups according to subspecialty. Results: We obtained a total of 468 valid questionnaires. For diagnosis, 24.4% have not initially requested any imaging method. The most requested exam was ultrasonography (54.9%). A non-surgical treatment was indicated for all the with great variability between their recommendations. For refractory cases, 78.3% of the respondents prefer doing a local infiltration. with corticosteroids (89.6%). Of the total respondents, 12.8% do not recommend surgical treatment for LE, and 75,8% of who does, indicate open techniques. Conclusion: Most orthopedists begin the treatment of lateral epicondylitis with the use of non-steroidal anti-inflammatory drugs, physical therapy, and an indication of rest, but there is great variability between their recommendations. The use of corticosteroids for infiltration remains the main choice among Brazilian orthopedists. Most of participants prefer the open technique for surgical treatment.